Women of the Bible from text to image - Seijas de los Ríos-Zarzosa, María Guadalupe; Walker Vadillo, Monica Ann (London [England] T&T Clark, 2022)
"The Hebrew Bible and art are at the core of this book, which analyzes the iconographic representation of several women of the Bible. The contributors consider the ways in which the biblical texts regarding these women had been read and understood through time and the means by which they were represented. Each study also explores the different values associated with these representations according to the problems, worries and concerns of each period. Drawing upon disciplines such as theology, philology or history of art, the essays within this volume provide a cross-sectional, plural and rich approach. In focusing upon iconographic representation, numerous visual cultures of the last millennium, and a close analysis of several integral biblical women such as Bathsheba, Moses' mother, the Pharaoh's Daughter, Ruth, Naomi and Deborah, and their lasting influence upon Western art and culture, this book pursues an understanding of the history of the transmission and reception of the Bible in general and of the women of the Old Testament in particular."--
List of Plates -- List of Contributors -- Preface - Guadalupe Seijas, Universidad Complutense de Madrid, Spain -- Acknowledgements -- List of Abbreviations -- Chapter 1: Bible, Art and Women: Biblical Analysis and Interpretation - Carmen Yebra, Universidad Pontificia de Salamanca, Spain -- Chapter 2: The Iconographic Representation of the Bible: the Interaction Between Text and Image - Guadalupe Seijas (Universidad Complutense de Madrid, Spain -- Chapter 3: Bathsheba in Medieval Manuscripts: Visual Analysis of a Controversial Character - Mónica Ann Walker, University of Oxford, UK -- Chapter 4: Strong Women of the Bible and their Persistence in the Spanish Painting of the 17th Century - Amparo Alba and Guadalupe Seijas, Universidad Complutense de Madrid, Spain -- Chapter 5: Moses' Mother and the Pharaoh's Daughter. Literary and Visual Reception in the 19th Century - Carmen Yebra, Universidad Pontificia de Salamanca, Spain -- Chapter 6: The Women in the Book of Judges and their Representation in the engravings in the 19th Century - Carmen Yebra, Universidad Pontificia de Salamanca, Spain -- Chapter 7: Ruth and Naomi: A Story of Friendship in Pictures - Guadalupe Seijas, Universidad Complutense de Madrid, Spain -- Conclusions -- Index
Barrierefreier Inhalt: Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Women in the Bible; Women and religion; Women -- Religious life; Aufsatzsammlung